Fuzzy logic and topographic data: susceptibility to soil salinization in the municipality of Jeremoabo, Bahia - de Jesus Pereira, Anderson [UNESP]; de Oliveira Junior, Israel; Bassoi, Luís Henrique; Costa, Taiara Souza (GN1 Sistemas e Publicacoes, 2022)
Topograp hic data extracted from a digital terrain model (DTM) make it possible to analyze factors associated with various phenomena arising on the earth’s surface. The aim of this study was to evaluate environmental susceptibility to soil salinization using the modeling of topographic data in the semiarid region of Brazil. The municipality of Jeremoabo, Bahia, was defi ned as the spatial scale for the analysis due to the climate characteristics and signs of environmental deterioration. The fuzzy gamma operator was applied to integrate the slope, plan and profi le curvature, and topographic wetness index, and to confi gure scenarios of susceptibility to salinization. Together, the classes of high and severe susceptibility to soil salinization occur in around 22.29% of the total area. They are associated with low slopes, high topographic wetness indices, a concave curvature profi le, and the planar class of plan curvature of the terrain. The data show the need to carry out effective land use planning for agriculture, such as the use of irrigation, to minimize the process of soil salinization, which is associated with the phenomenon of desertifi cation
Lógica fuzzy e dados topográfi cos: susceptibilidade à salinização dos solos no município de Jeremoabo-BA
Keywords: Environmental analysis; Fuzzy logic; Geoprocessing; Salinity